The Development of an Activity Model to Encourage Reading Habit Focusing on Coaching for Senior High School Students - Vilavan, Naowarat; Yuankrathok, Panadda; Kuroda, Ariyabhorn (Journal of Ecohumanism, 2025)
This current research is research on the development of an activity model to encourage reading habits focusing on coaching for senior high school students. It aims to: 1) study the effectiveness of the reading habit promotion activity model that emphasizes coaching for high school students in terms of reading habit, 2) study the effectiveness of the reading habit promotion activity model with emphasis on coaching for high school students in terms of satisfaction. Qualitative research methods were used, including document and field data collection was 1) synthesizing basic information to determine the format of the activity to promote reading habits that emphasize coaching from documents and related research, 2) designing and finding the effectiveness of the format of the activity to promote reading habits that emphasize coaching from the appropriateness assessment using a 5-level rating scale assessment form from experts, 3) using the draft format to test the activity (try out) with the target group of 20 high school students, and 4) using the format to organize activities and finding the effectiveness of the format of the activity to promote reading habits that emphasize coaching from the target group of 20 high school students. The findings showed that The developed reading habit promotion activity model with an emphasis on coaching for high school students has 7 components: 1) the basic concept and theory of the activity model, 2) the objective of the activity model, 3) the activity content, 4) the activity process, 5) the social system and the response principle, 6) the support system or environment, and 7) the results for the learners. There are 5 steps in organizing the activity: 1) analyzing the basic data of each coach, 2) setting goals and action plans, 3) implementing the coaching process, 4) debriefing and developing the process, and 5) giving rewards to the learners. The effectiveness of the reading habit promotion activity model with an emphasis on coaching for high school students is at the most appropriate level. The effectiveness of the reading habit promotion activity model that emphasizes coaching for high school students was found to be that all students passed the reading habit assessment criteria at the highest level ( at 91.00 percent. The satisfaction of students, teachers, and parents with the format of the activity was at the highest level overall ( , the percentage was 92.80, indicating that the developed reading promotion activity format can promote reading habits.